ASTM designation D6173-97 : Standard test method for determination of various anionic surfactant actives by potentiometric titration. (West Conshohocken (Pa.) : ASTM International)
1.1 This test method is based on a potentiometric titration of common anionic surfactants and blends of anionic surfactant with a hydrotrope. This test method solely is intended for the analysis of active matter in the following surfactants: alcohol ether sulfate, alpha olefin sulfonate, alkylbenzene sulfonate/sodium xylene sulfonate blend (5:1), sodium alkylbenzene sulfonate/sodium xylene sulfonate blend (16:1), and sodium alkylbenzene sulfonate/sodium xylene sulfonate blend (22:1). It has not been tested for surfactant formulations.
Keywords: Normen